The effect of the number of active electrode poles during tined lead placement on long‐term efficacy of sacral neuromodulation in patients with faecal incontinence. (22nd July 2020) - Assmann, R.; Breukink, S. O.; Caubergh, S. A. P.; Stassen, L. P. S.; van Kuijk, S. M. J.; Melenhorst, J.
Abstract: Aim: There is an ongoing debate as to whether or not the efficacy of sacral neuromodulation (SNM) is optimized by maximizing the total number of active electrode poles (AEPs) during lead placement because there are more programming options. However, this is at the cost of increased operating time. The aims of this study were to establish if a higher number of AEPs improves SNM efficacy during the trial period and after permanent implantable pulse generator (IPG) placement and if there is there a correlation between number of AEPs and battery life of the first placed IPG. Method: This was a single centre retrospective cohort study of new patients with faecal incontinence who underwent SNM between 2000 and 2018. Exclusion criteria were sphincter defect > 30%, rectocele/enterocele Grade 3 or higher and incomplete records. Results: In all, 288/456 (63%) patients (women 91%; mean age 58.5 ± 11.7 years) were eligible for analysis. The number of AEPs during lead placement was two ( n  = 42, 14.5%), three ( n  = 82, 28.5%) and four ( n  = 164, 57%). There was no association between the number of AEPs during tined lead placement and long‐term efficacy. Neither the success rate of the trial phase nor the battery life after first placed IPG was influenced by the number of AEPs. Conclusion: In this study, the number of AEPs does not seem to influence long‐term efficacy of SNM success rate during the trial phase or the battery life of the first placed IPG. However, we also suggest that at the very least there should be two AEPs at lead placement.